Machine learning algorithm for soybean leaf disease detection: Machine learning algorithm for soybean leaf disease detection - PREETI JHA; ARUNA TIWARI; NEHA BHARILL; MILIND RATNAPARKHE; OM PRAKASH PATEL; UDAY KUMAR REDDY; SHRAVYA RAMASAHAYAM (Journal of Oilseeds Research, 2023)
Agriculture is now the primary source of income for nearly 45% of India’s population. This makes it important to aid farmers with crop cultivation, protection, and harvesting. Soybean is one of the most widely grown plants in India, especially in the states of Madhya Pradesh and Maharashtra. But soybean crops are prone to diseases like yellow mosaicand anthracnose, amongst others. We propose hybrid deep learning algorithm to detect diseases in soybean plant leavesusing computer vision techniques. In the experimentation, various classification algorithms were compared using accuracy.